Ekspolitasi Tubuh, Iklan, dan Gangguan Kesehatan Mental, dalam Film Tusk (2014) - Indra Miftahul Fadli; Lathifa Prima Ghanistyana; Pradikta Aqsal Alrasyid; Muhamad Rifki Maulana (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
The representation of bodily exploitation in visual media is a significant issue in contemporary communication studies, particularly when linked to social pressures and mental health. This research aims to analyze the representation of bodily exploitation and psychological disorders in the film Tusk (2014), as well as how the film’s narrative and visual elements convey criticism of media and advertising culture. Using a qualitative descriptive approach and Roland Barthes' semiotic analysis method, this study explores the denotative, connotative, and mythological meanings of cinematic symbols. The findings indicate that Tusk represents the human body as an object of manipulation that loses its humanity. The protagonist’s physical transformation into a walrus serves as a symbol of dehumanization caused by past trauma and social pressure. Cinematographic techniques and grotesque visual symbols intensify the atmosphere of psychological suffering experienced by the character. This study concludes that Tusk is not merely a horror film, but also a reflective medium that voices the importance of empathy, awareness of trauma's impact, and the protection of bodily integrity in visual culture. These findings are relevant in expanding the understanding of how media shapes perceptions of the body and mental health.